2016
DOI: 10.3389/fmicb.2016.00106
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Gβ-Like Protein CpcB Involved in Antifungal Drug Susceptibility and Virulence in A. fumigatus

Abstract: Aspergillus fumigatus is an airborne human fungal pathogen that can survive in a wide range of environmental condition. G protein complex transduces external signals from a variety of stimuli outside a cell to its interior effectors in all eukaryotes. Gβ-like CpcB (cross pathway control B) belongs to a WD40 repeat protein family with the conserved G–H and W–D residues. Previous studies have demonstrated that Gβ-like proteins cooperate with related signal transduction proteins to function during many important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Notably, it is one of the most prevalent airborne fungal pathogens, causing severe (usually fatal) invasive aspergillosis in immune compromised individuals (Ellett, Jorgensen, Frydman, Jones, & Irimia, 2017;Hillmann et al, 2015;Long, Xu, Zeng, Sang, & Lu, 2017;Throckmorton, Lim, Kontoyiannis, Zheng, & Keller, 2016). It has been identified that the virulence determinants of A. fumigatus are dependent on both fungal biological characteristics and host immune status (Cai et al, 2016). Among these virulence determinants, the ability of pathogens to acquire and detoxify metal ions within the host micro-environment is important for pathogen survival, proliferation, and subsequent virulence (Amich et al, 2014;Ding, Festa, Sun, & Wang, 2014;Wiemann et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, it is one of the most prevalent airborne fungal pathogens, causing severe (usually fatal) invasive aspergillosis in immune compromised individuals (Ellett, Jorgensen, Frydman, Jones, & Irimia, 2017;Hillmann et al, 2015;Long, Xu, Zeng, Sang, & Lu, 2017;Throckmorton, Lim, Kontoyiannis, Zheng, & Keller, 2016). It has been identified that the virulence determinants of A. fumigatus are dependent on both fungal biological characteristics and host immune status (Cai et al, 2016). Among these virulence determinants, the ability of pathogens to acquire and detoxify metal ions within the host micro-environment is important for pathogen survival, proliferation, and subsequent virulence (Amich et al, 2014;Ding, Festa, Sun, & Wang, 2014;Wiemann et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The G β -CpcB protein was recently shown to be involved in cell-wall integrity and virulence of A. fumigatu s. 55 Interestingly, the increased fold change in the interaction of calcium/calmodulin-dependent protein kinase with calcineurin only in the presence of CSP (5.6-fold; Supplementary Table 1, sheet 5) and MFG (5.2-fold; Supplementary Table 1, sheet 6) but not following VOR treatment also indicated differential calcineurin interactions between the azole and the echinocandin treatments. The DUF89 protein, whose function remains unknown, was also increased two-fold in VOR treatment in comparison with the control (Table 3), but not in CSP and MFG treatment.…”
Section: Resultsmentioning
confidence: 99%
“…For double deletions of tpo3 and dur3 , a similar strategy was used. The dur3 deletion cassette was generated using upstream fragment, the hygromycin B resistance gene hph selectable marker amplified from the plasmid pAN7-1 ( Cai et al, 2016 ) using primers hph F + hph R, and downstream fragment. The dur3 deletion cassette was then transformed into the background of an tpo3 -deleted mutant and transforments were screened using 300 μg ml –1 of hygromycin B.…”
Section: Methodsmentioning
confidence: 99%